2022
DOI: 10.28991/hij-2022-03-03-09
|View full text |Cite
|
Sign up to set email alerts
|

An Investigating of the Impact of Bed Flume Discordance on the Weir-Gate Hydraulic Structure

Abstract: Discordance and concordance play a significant role in the hydraulic response for the flume, open channel, hydraulic structure, and flow field measurement. Bed discordance and bed concordance are regarded as common problems in open channels. Discordance is the dominant one, which could have an effect on the hydraulic structure that is constructed inside the channel. This paper deals with the impact of bed flume discordance on hydraulic flow characteristics at the weir-gate downstream hydraulic regime. Four con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…As the water depth increases, the Froude number will decrease due to the inversely proportional relationship between them. For model (5), which has Ag/BH = 0.088 and d = 3cm. in case (1), the maximum value of Fr is 1.21 and the maximum value of Fr is 0.4 for all cases 2, 3, and 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the water depth increases, the Froude number will decrease due to the inversely proportional relationship between them. For model (5), which has Ag/BH = 0.088 and d = 3cm. in case (1), the maximum value of Fr is 1.21 and the maximum value of Fr is 0.4 for all cases 2, 3, and 4.…”
Section: Resultsmentioning
confidence: 99%
“…The inclination angle refers to the angle between the combined hydraulic structure and the horizontal bed of the flume. Qasim et al [5] did some experiments to study the influence of the bed flume contraction on the combined structure discharge coefficient, also this work also dealt with Reynolds number, Froude number, actual discharge, flow velocity and downstream water depth. Yossef and de Vriend [6] performed experimental investigation in order to study the flow pattern for both submerged and emergent groynes.…”
Section: Introductionmentioning
confidence: 99%
“…here, the length and thickness of the obstacle is considered changeable while the width is constant. Qasim et al [6] investigated how the combined hydraulic will be influence by the discordance of the bed flume, the investigation dealt with hydraulic characteristics at the downstream of the combined structure. Notably, every published research has demonstrated that machine learning systems can reliably predict Cd.…”
Section: Introductionmentioning
confidence: 99%